FENOMENA PEMBAJAKAN HAK CIPTA KARYA MUSIK DALAM BENTUK VCD DAN DVD: SUATU KAJIAN SOSIOLOGIS DARI TIDAK MAKSIMALNYA SANKSI HUKUM - oksidelfa Yanto (Jurnal Surya Kencana Dua : Dinamika Masalah Hukum dan Keadilan, 2016)
The number of piracy cases are popping up in the environment community indicates malfunctioning of the Act or law in mengujudkan legal protection of copyright musical works. It makes people increasingly do not trust the government officials there. Whereas cases of music copyright piracy is certainly not to be taken lightly. If left Indonesia will be increasingly threatened by the danger of a prolonged legal harassment, and it would threaten the creativity of the people of this country. Type commonly violated copyright piracy cassette production CD, VCD and DVD. Perederan proliferation of pirated goods in places such open indication can be seen from the market dominated by pirates. Keywords: Piracy, copyright, Sanctions Law